The Role of Teachers in Developing Students' Interest in Learning Through Project-Based Learning in the Merdeka Curriculum in Elementary Schools - Ningsih, Desi Afriani; Fitriana, Maulida Arum; Dwipa, Lalu Belik Made (International Journal of Education, Information Technology, and Others, 2025)
This study aims to describe the role of teachers in developing students' interest in learning through project-based learning in the Merdeka Curriculum. The focus of this study is the role of teachers as facilitators and motivators in creating an active, creative, and enjoyable learning environment. The method used in this study is a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results of the study indicate that teachers play a crucial role in guiding and facilitating students. The role of teachers has proven effective in increasing student participation, fostering curiosity, and nurturing a passion for learning. Thus, the role of teachers is highly strategic in developing students' interest in learning through project-based learning in the Merdeka Curriculum